2022
DOI: 10.1186/s13287-022-03025-5
|View full text |Cite
|
Sign up to set email alerts
|

Cyst stem cell lineage eIF5 non-autonomously prevents testicular germ cell tumor formation via eIF1A/eIF2γ-mediated pre-initiation complex

Abstract: Background Stem cell niche maintains stem cell population identity and is essential for the homeostasis of self-renewal and differentiation in Drosophila testes. However, the mechanisms of CySC lineage signals-mediated soma–germline communications in response to external stimuli are unclear. Methods Pre-initiation complex functions were evaluated by UAS-Gal4-mediated cell effects. RNA sequencing was conducted in NC and eIF5 siRNA-treated cells. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…5A), leading to the differentiation defects of elongated spermatids. Orb was used as a classical marker with highly enriched expression level in elongated spermatids [23,32]. Our results showed that the expression pattern of Orb protein was disturbed at late stage of spermatogenesis in control and Sb-exposed testes (Fig.…”
Section: Spermatid Cell Profiling Revealed Molecular Signatures Follo...mentioning
confidence: 56%
See 3 more Smart Citations
“…5A), leading to the differentiation defects of elongated spermatids. Orb was used as a classical marker with highly enriched expression level in elongated spermatids [23,32]. Our results showed that the expression pattern of Orb protein was disturbed at late stage of spermatogenesis in control and Sb-exposed testes (Fig.…”
Section: Spermatid Cell Profiling Revealed Molecular Signatures Follo...mentioning
confidence: 56%
“…DNA staining highly condensed at the early-stage nuclei of germ cells and the nuclei of clusters of elongated spermatozoa in the Drosophila testis [16,23]. Based on the above observation, we next counted the number of elongated spermatid clusters and found a significant and dose-dependent decrease (Fig.…”
Section: Cellular Effects Of Sb Exposure In Drosophila Testesmentioning
confidence: 76%
See 2 more Smart Citations
“…Drosophila oo18 RNA-binding protein (Orb) and Orb2 are two highly conserved RNA-binding proteins belonging to the cytoplasmic polyadenylation element binding (CPEB) protein family, which plays a critical role in mRNA transport and local translation [55]. Both Orb and Orb2 are highly enriched in elongated spermatids and regulate spermatogenesis [22,56]. Immunofluorescence staining in the Drosophila testis shows that Orb and Orb2 proteins have low levels of expression in mitotic spermatogonia and extremely high levels in elongated spermatids.…”
Section: Axoneme Assemblymentioning
confidence: 99%